2019
DOI: 10.1016/j.wear.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of mechanical properties induced by friction in the Archard wear model

Abstract: Fretting is small-amplitude, oscillatory motion between two bodies leading to surface damage. During the fretting process, a tribologically transformed structure (TTS) which has different mechanical properties and microstructure than the starting material is formed on the surface. The commonly-used Archard wear equation relating wear volume to the hardness of the worn material does not account for changes in mechanical properties induced by friction in fretting. To investigate that effect, ball-on-plane fretti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 45 publications
(56 reference statements)
1
31
0
Order By: Relevance
“…The evolution of mechanical properties and microstructures of tribologically transformed structure (TTS) layers during fretting process were investigated using nanoindentation and focused ion beam-scanning electron microscope (FIB-SEM). A modified wear model that accounts for friction-induced dynamic changes in mechanical properties was proposed [206]. In Ref.…”
Section: Wear Behavior and Mechanismsmentioning
confidence: 99%
“…The evolution of mechanical properties and microstructures of tribologically transformed structure (TTS) layers during fretting process were investigated using nanoindentation and focused ion beam-scanning electron microscope (FIB-SEM). A modified wear model that accounts for friction-induced dynamic changes in mechanical properties was proposed [206]. In Ref.…”
Section: Wear Behavior and Mechanismsmentioning
confidence: 99%
“…In previous studies [37][38], it has been shown that copper under friction loading can cause the material to harden in the contact area with a low volume of wear. This can also be confirmed in this study with very low wear, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reiterated the potential usefulness in measuring wear in situ rather than relying on post-test profilometry measurements [19,20]. In wear prediction it is often assumed that the wear rate is linear but this is generally not the case, particulary when there is a change in the predominant wear mechanism during the test [20,21]. Table 1 compares the typical conditions in the new capability for nano-scale reciprocating wear to other approaches for multi-pass sliding contacts (repetitive scratch and nano-fretting) with the same instrumentation.…”
Section: Instrument Developmentmentioning
confidence: 99%
“…The surface/near surface microstructure of the alloy may also evolve during sliding and influence the friction. With continued sliding grain refinement and/or formation of a tribologically transformed structure (TTS) has been reported for many alloys [14,21,26,[28][29][30][31][32]. Suresh and co-workers have reported grain refinement resulting in an increase in hardness within the scratch track on Cu [26,30].…”
Section: Influence Of Surface Topography and Ploughing On Friction Evolutionmentioning
confidence: 99%
See 1 more Smart Citation